2005
DOI: 10.1177/0305735605048015
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and perception in post-tonal music: an example from Kurtág’s String Quartet Op. 1

Abstract: In this study, two different types of analysis of a piece of post-tonal music (the fifth movement of the String Quartet Op.1 (1959) by G. Kurtág) are compared: an analysis performed by seven professional music analysts using the musical score, and a perceptual analysis carried out by two groups of subjects (18 musicians and 25 non-musicians) while listening in real time. Three possible macroforms proposed by the analysts were compared with those perceived by the listeners. The results show that the macroforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Thus, HF accents work as cues that affect the perception of the overall structure of the piece. These results are in line with our previous studies on the memorization of the overall structure (Addessi and Caterina, 2000, 2005). Instead, surprisingly, it seems that the strong beat (SB) does not affect the perception of the strong accents more than the weak beat (WB).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, HF accents work as cues that affect the perception of the overall structure of the piece. These results are in line with our previous studies on the memorization of the overall structure (Addessi and Caterina, 2000, 2005). Instead, surprisingly, it seems that the strong beat (SB) does not affect the perception of the strong accents more than the weak beat (WB).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous experimental studies, we analyzed how the listeners (musicians and non-musicians) memorize the overall structure of post-tonal music during listening in real time (Addessi and Caterina, 2005; Addessi, 2010). We observed that the perception of “prominent features” allowed the listeners to perceive several points of segmentations, to divide the piece into the main sections and consequently, to memorize the overall structure of the musical piece.…”
Section: Introductionmentioning
confidence: 99%
“…Hargreaves and North (1999) conclude that the psychological functions of music embrace three broad domains, specifically cognitive, emotional and social functions. Functions of music listening in the cognitive domain are investigated in studies on the perception, recognition and memory of musical elements and characteristics, such as pitch, melody, rhythm, structure or complexity (e.g., Addessi & Caterina, 2005; Deliège & Sloboda, 1997; Ockelford, 2004); the immanent ability of music to trigger autobiographical memory (Cady, Harris, & Knappenberger, 2008; Schulkind, Hennis, & Rubin, 1999); and music’s influence on cognitive performance (Furnham & Stephenson, 2007; Lesiuk, 2005; Schellenberg, Nakata, Hunter, & Tamoto, 2007). The emotional domain receives attention in studies about emotions perceived in music, emotions and physical reactions induced through music and emotions expressed through music (Juslin, 2005; Juslin & Laukka, 2004; Nawrot, 2003).…”
Section: The Functions Of Music Listening: Three Levels Of Musical Experiencementioning
confidence: 99%
“…The division into parts of a tonal piece largely depends, however, on formal (and cultural) rules (exposition, development, conclusion, coda, recapitulation, bridge, repetition, symmetry, etc.). Traces of these cultural rules may, in fact, persist in posttonal music (Baroni 2003, Addessi and Caterina 2005, Imberty 2005, Lalitte et al 2009). …”
Section: The Perception Of Macroform In Post-tonal Musicmentioning
confidence: 99%
“…By working on such a homogeneous repertoire, the number of variables is limited and it is therefore easier to formulate plausible and general hypotheses about the problems of listening to post-tonal music. In Addessi & Caterina (2005) a comparison was made between the macroformal analyses of the fifth movement of the String Quartet Op. 1 by G. Kurtág, carried out by several professional music analysts from different Italian universities, and those perceived by two groups of subjects (musicians and not musicians) while listening to the piece in real time.…”
Section: Macroform Analysed and Macroform Perceivedmentioning
confidence: 99%